A Comparative Study on Noise Pollution during Festival of Light and COVID-19 in the Himalayan City of Dehradun - Kapil Kumar Joshi; Amit Pokhriyal (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
This article aims at analyzing the level of sound pollution at six major locations of Dehradun city, a Himalayan district of Uttarakhand, India. The study is based upon the collection of real-time data by the state’s pollution control board during and before the Coronavirus generated lockdown conditions. On analyzing data, it reveals tranquility attained by the city during lockdown conditions. The study also swings on two extremes by comparing lockdown duration noise data with one of the noisiest times i.e., during Deepawali, the festival of lights, and firecrackers. An attempt to sketch a brief technical note on the harmful effects of noise pollution and measures to check it through manmade interventions is also made in this paper.